Parallelism error in peanut sowing operation with auto-steer guidance - Santos, Adao F. dos [UNESP]; Silva, Rouverson P. da [UNESP]; Tavares, Tiago O. [UNESP]; Ormond, Antonio T. S. [UNESP]; Rosalen, David L. [UNESP]; Assis, Leonardo C. de (Univ Federal Campina Grande, 2017)
GNSS positioning errors are certain, regardless of the adopted positioning method. In agriculture, these errors may represent higher or lower overlapping rates between passes of a mechanical assembly, affecting operation quality. Therefore, this study evaluated the main errors arising from peanut sowing operation performed with an auto-steer guidance system by an RTX signal, using the Statistical Process Control techniques. The errors evaluated were: in tractor lateral displacement, project execution, and parallelism between passes of tractor-seeder set. The average errors of project execution in all passes were within the range specified by the manufacturer, i.e. lower than 3.8 cm. The average error of tractor-seeder set was also within the accepted range. However, as shown in control charts, lateral tractor displacement had interference of terrain slope, causing average errors higher than the accepted range. Based on the control charts, project execution accuracy was satisfactory, and it is possible to use the RTX signal in agricultural operations that require accuracy lower than 3.8 cm, such as peanut sowing.
Keywords: autopilot; precision agriculture; electric auto-steering; RTX; GNSS